The Reflection of Social Problems in the Novels by S. Maugham - Gunay İsmayilova (Program Studi Pendidikan Bahasa Inggris, STKIP Kie Raha Ternate, 2022)
The article analyzes the impact of the social environment on human life, the struggle of man to find his place in society in the novels of the English writer W.S. Maugham, who lived on the threshold of two centuries and skillfully reflected the characteristics of both realism and romanticism in his work. The inner world of the heroes, the principles of their existence in society, the impact of the environment on human life, regardless of age, as well as serious problems such as human collisions with the environment in the prose examples of the writer who deeply understands the essence of the problems of man and society, pays attention to the socio-philosophical harmony of life and the world are the object of research. The struggle for life and rebellion of the heroes against the accepted laws of society were emphasized based on the author's novels such as “The Moon and Sixpence”, “Theatre”, “Cakes and Ale” , “Liza of Lambeth”. At the same time, the article identifies the forms of manifestation of human and social problems against the background of social features and reveals the mechanism of conflict. The attitude of various writers and critics to Maugham's work was also touched upon.